"Inextricably Intertwined": Response to "The Work of Visual Art in Liturgy" by Deborah Sokolove. (March 2022) - McFee, Marcia
Our ancient ancestors instinctively enacted their stories onto and within walls that resonated with the sound, and reflected the light, of their gatherings. Those of us who care for the liturgical needs of our communities have the same task and, I believe, are instinctively compelled by the same Spirit. We call on all of the senses through every expressive medium we have at our disposal—the arts of color, texture, line, movement, intonation, inflection, crescendo and legato. We curate symbolically-significant occasions and act as prompters for the participation of the people in their ritual art-making. We do it because it is what we have always done, because we can't not do it, and if we are not doing it, it is because it is being actively suppressed by our own or other's notions about what is "right and good." The relationship of liturgy and the arts is not primarily a conversation between entities, but an inextricable part of our very anima, our pneuma . The stories handed down to us come alive when we come alive.